Strategies to manage the evolution of glyphosate resistance in New Zealand - Harrington, K.C.; James, T.K.; Parker, M.D.; Ghanizadeh, H. (New Zealand Plant Protection, 2016)
The first cases of weeds developing resistance to glyphosate within New Zealand have recently been reported and investigated Both perennial ryegrass (Lolium perenne) and Italian ryegrass (Lolium multiflorum) populations have become resistant to glyphosate in several Marlborough vineyards due to many years of weed control using mainly just glyphosate Glyphosate is currently being used in many situations throughout New Zealand that could easily lead to further resistance developing such as in other perennial fruit crops on roadsides railways amenity areas waste areas fence lines and headlands of crops Following wide consultation as part of a Sustainable Farming Fund project strategies for resistance management in three systems (vineyard and orchards amenity and waste areas and crops and pastures) are suggested Adoption of these strategies will allow glyphosate to continue as a useful herbicide in New Zealand